Home advantage in the Icelandic basketball association men´s premier league - Margrét Harðardóttir 1975- (2014)
Home advantage is well-established in the world of sports, but has not been studied in Iceland; previous studies have shown more so in team sports than individual sports. The focus of this study is the outcome of games on the home court. The aim of this study is to find out if there is a home court advantage in The Icelandic Basketball men’s premier league. Two methods of calculation are used. First one is to analyze if the teams won more games at home than away. The second is to analyze if they won more games at home than they lost at home. The population of the study is all teams in the men’s top league in Iceland, a total of 23 teams. Aggregated results of 6816 games, from 26 seasons, both at home and away with emphasis on home court wins were used for calculation of home court advantage. Three teams played all 26 seasons. These three are analyzed especially to see if there are any trends or variance during the 26 seasons. Two methods are used to calculate home court advantage within the league and for individual teams for the 26 seasons, respectively. A Method 1of calculation is number of games won at home of all games won for each team. Method 2 of calculation is number of games won at home of all games played at home for each team (phase 2). A review of the literature shows that these two methods have not been used before to calculate home court advantage. Together method 1 and 2 of calculation give reliable results (p≥0,05) when used in calculating home advantage in basketball for the whole league and each team expressed as average percentage. The main result of this study is that there is an advantage in playing on home court in The Icelandic Basketball men’s premier league (58%-61%, p≥ 0,05). Individual team results, expressed as average percentages show a great variability (43%-63%, p≤ 0,05), which may tell us more about the different quality or ability of the teams than about home court advantage. The ability of the teams also happens to be the major cause of problems in accurate measurements of home ...